Borderline Personality Disorder of Josh's Character in Sonia Mael's No Ordinary Love Novel - Rohmah, Tsaniah Yaumil; Oktafiyani, Elve (Vivid: Journal of Language and Literature, 2023)
This research aims to investigate the psychological conditions of Josh's character in Sonia Mael's No Ordinary Love novel through borderline personality disorder theory by John G. Gunderson. A borderline personality disorder is an intense emotional dysregulation that can affect someone's personality. The research uses a qualitative method, and the writers are the instrument themselves. In order to analyse Josh's character, the writers use the characterisation theory by Richard Gill. Besides that, the writers focus on character psychological problems with borderline personality disorder theory by John G. Gunderson, which has several concepts; signs and symptoms, causes and impacts, and its developed traits. The result of the research is that Josh's character has a distortion in his personality growth because of his childhood trauma which developed his personality and emotion in what he experienced and perceived. As an educated person, he is good at positively managing things, as his thoughts try to stay sane in living his life. However, his emotional-behavioural management is disturbed by how his experience and self-growth developed his perceptions. In addition, he has developed all nine signs and symptoms of BPD which is also added by several other traits associated with how he acted out as a high-functioning BPD type. Although he has grown up unconsciously developing it, the positive traits also remain to keep it together in himself. In sum, his behaviour is proven to be borderline personality disorder symptoms caused by the personality growth he passed since traumatic experiences in his childhood.